2011
DOI: 10.1186/1756-0500-4-127
|View full text |Cite
|
Sign up to set email alerts
|

Hand Grip Strength: age and gender stratified normative data in a population-based study

Abstract: BackgroundThe North West Adelaide Health Study is a representative longitudinal cohort study of people originally aged 18 years and over. The aim of this study was to describe normative data for hand grip strength in a community-based Australian population. Secondary aims were to investigate the relationship between body mass index (BMI) and hand grip strength, and to compare Australian data with international hand grip strength norms.MethodsThe sample was randomly selected and recruited by telephone interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
402
12
27

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(480 citation statements)
references
References 22 publications
39
402
12
27
Order By: Relevance
“…Grip strength was measured using a Sammons Preston Swedley-Type hand dynamometer (Jamar ® , Bolingbrook, IL, USA) 24,25 . The test was performed three times on the dominant upper limb at 10-second intervals between each run.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Grip strength was measured using a Sammons Preston Swedley-Type hand dynamometer (Jamar ® , Bolingbrook, IL, USA) 24,25 . The test was performed three times on the dominant upper limb at 10-second intervals between each run.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The larger muscle mass will lead to larger muscle strength. 9,15 The highest correlation was found between Jamar grip strength and sphygmomanometer with a correlation coefficient of 0.835. This supports the prediction of Jamar grip strength value using the sphygmomanometer.…”
Section: Discussionmentioning
confidence: 81%
“…8 Another study in Australia presents a different result as it is able to discover the presence of association between grip strength and body mass index; however, their normative value is lower than that of the international literature. 9 The standard instrument to measure grip strength worldwide is Jamar dynamometer. 10 However, Jamar is rarely found in developing countries such as Indonesia.…”
Section: Original Articlementioning
confidence: 99%
“…MassyWestropp and others [9] found that hand grip strength was higher in the right hand, regardless of hand dominance. On the other hand, the 10% hand dominance rule indicating that the dominant hand has 10% more powerful grip than the non-dominant one [11], was shown in a review of ten studies to be true for right dominant subjects.…”
Section: Dominant Hand Differencesmentioning
confidence: 79%